Persistence of Yellow fever virus outside the Amazon Basin, causing epidemics in Southeast Brazil, from 2016 to 2018. - Izabela Maurício de Rezende; Lívia Sacchetto; Érica Munhoz de Mello; Pedro Augusto Alves; Felipe Campos de Melo Iani; Talita Émile Ribeiro Adelino; Myrian Morato Duarte; Ana Luísa Furtado Cury; André Felipe Leal Bernardes; Tayrine Araújo Santos; Leonardo Soares Pereira; Maria Rita Teixeira Dutra; et al. (Public Library of Science (PLoS), 2018)
Yellow fever (YF) is endemic in the Brazilian Amazon Basin, and sporadic outbreaks take place outside the endemic area in Brazil. Since 2016, YF epidemics have been occurring in Southeast Brazil, with more than 1,900 human cases and more than 1,600 epizooties of non-human primates (NHPs) reported until April 2018. Previous studies have demonstrated that Yellow fever virus (YFV) causing outbreaks in 2017 formed a monophyletic group.Aiming to decipher the origin of the YFV responsible for the recent epidemics, we obtained nucleotide sequences of YFV detected in humans (n = 6) and NHPs (n = 10) from Minas Gerais state during 2017-2018. Next, we performed evolutionary analyses and discussed the results in the light of epidemiological records (official numbers of YFV cases at each Brazilian Federative unit, reported by the Brazilian Ministry of Health). Nucleotide sequences of YFV from Southeast Brazil from 2016 to 2018 were highly conserved and formed a monophyletic lineage (BR-YFV_2016/18) within the genotype South America I. Different clusters were observed within lineage BR-YFV_2016/18, one containing the majority of isolates (from humans and NHPs), indicating the sylvatic transmission of YFV. We also detected a cluster characterized by two synapomorphies (amino acid substitutions) that contained YFV only associated with NHP what should be further investigated. The topology of lineage BR-YFV_2016/18 was congruent with epidemiological and temporal patterns of the ongoing epidemic. YFV isolates detected in 2016, in São Paulo state were located in the most basal position of the lineage, followed by the isolates from Minas Gerais and Espírito Santo obtained in 2017 and 2018. The most recent common ancestor of the lineage BR-YFV_2016/18 dated to 2015 (95% credible intervals = 2014-2016), in a period that was coincident with the reemergence of YFV in the Midwest region of Brazil.The results demonstrated a single introduction of YFV in the Southeast region and the silent viral circulation before the onset of the outbreaks in 2016. Evolutionary analyses combined with epidemiological records supported the idea that BR-YFV_2016/18 was probably introduced from the Midwest into the Southeast region, possibly in São Paulo state. The persistence of YFV in the Southeast region, causing epidemics from 2016 to 2018, suggests that this region presents suitable ecological and climatic conditions for YFV maintenance during the epidemic and interepidemic seasons. This fact poses risks for the establishing of YF enzootic cycles and epidemics, outside the Amazon Basin in Brazil. YF surveillance and studies of viral dynamics deserve particular attention, especially in Midwest, Southeast and neighbor regions which are the main areas historically associated with YF outbreaks outside the Amazon Basin. YFV persistence in Southeast Brazil should be carefully considered in the context of public health, especially for public health decision-makers and researchers.